A New Heligmonellid (Nematoda) from Sylvilagus floridanus (Leporidae) in Costa Rica, with Some Comments on Species of Paraheligmonella Durette-desset, 1971 - Digiani, Maria Celina (2009)
Paraheligmonella kinsellai n. sp. (Nematoda: Heligmonellidae: Heligmonellinae) is described from the small intestine of a cottontail rabbit Sylvilagus floridanus  (Allen, 1890) (Leporidae) from Costa Rica. The new species is similar to P. romerolagi (Gibbons and Kumar, 1980), parasitic in Romerolagus diazi from Mexico and to P. lamothei Digiani, Carren˜o, and Durette-Desset, 2008, parasitic in Sylvilagus floridanus from Costa Rica, by the characters of the synlophe at mid-body, i.e., 14 cuticular ridges and a single axis of orientation inclined at 30 to the sagittal axis in both sexes. The males of the new species are distinguished from those of P. romerolagi by a caudal bursa that is not bell-shaped, a bursal pattern of type 2–3 with a tendency to 2–2–1, and a genital cone that is not hypertrophied. They are also distinguished from the males of P. lamothei by having the same bursal pattern in both lobes (in P. lamothei the pattern is 2–2–1 on the right lobe and 2–3, with a tendency to 2–2–1, on the left lobe), rays 3 are much longer than rays 2, rays 2 and 3 diverging more proximally, and rays 8 are longer than the dorsal ray. The females of the new species also differ from those of P. lamothei by the shape of the posterior extremity (long and strongly curved vs. short and nearly straight) and by the synlophe at the ovejector level (ridge no. 1 hypertrophied and remaining ridges reduced vs. ventral ridges hypertrophied and dorso-lateral ridges reduced).